Evaluating Public Participation in a Project Plan Review: A Nigerian Case Study - Adewumi I. Badiora; Abdullateef I. Bako; Daniel O. Olaleye (Journal of MultiDisciplinary Evaluation)
Background:  Rooted in national and international laws regarding project planning and implementation is public participation. However, it is unclear whether public projects are enabling sufficient public input or are likely to be able to meet future management planning needs; particularly in developing countries.